경기도 자동심장충격기의 설치 및 사용과 사회경제적 수준의 연관성 분석 - 신현남 (The Graduate School, Ajou University, 2024)
배경 및 목적 : 2021년 병원 전 급성심장정지 환자의 23%가 경기도에서 발생하였다. 급성심장정지 환자는 골든타임 4분 이내 심폐소생술과 제세동이 이루어지면 생존율을 70%까지 올릴 수 있으며, 환자 발견 즉시 자동심장충격기를 사용하여 제세동을 적용하면 생존율도 높고 신경학적 예후가 좋고 퇴원율이 높다고 알려져 있다. _x000D_ 본 연구에서는 경기도 시·군·구 자동심장충격기 설치와 지역주민의 사용 현황을 분석하고 사회경제적 수준의 연관성을 파악하여 지역주민 누구나 손쉽게 자동심장충격기에 접근하고 사용할 수 있도록 지역사회 프로그램 개발을 위한 기초자료로 활용하고자 수행되었다._x000D_ _x000D_ 방법 : 2019∼2022년 4년간 경기도에 설치된 자동심장충격기 위치 정보와 사용 현황은 중앙응급의료센터 응급의료 통계연보 및 인트라넷 등록대장을 이용하였으며 연구 대상 기간 동안 경기도에 설치되어 있는 자동심장충격기 중 이동 및 특수목적을 위하여 119구급차 및 의료기관 구급차에 설치된 자동심장충격기와 사설구급차에 설치된 자동심장충격기는 일반인 활용이 불가능한 자동심장충격기로 연구 대상에서 제외하였다. 응급실 내원 심정지 환자 생존 현황은 국가응급진료정보망(NEDIS) 등록자료를 이용하여 분석하였다. 사회경제적 수준을 나타내는 지표로 지역박탈지수를 5분위로 구분하였으며 지역박탈지수와 사회경제적 수준은 반비례하여 지역박탈지수가 높은 그룹은 사회경제적 수준이 낮은 그룹을 의미한다._x000D_ _x000D_ 결과 : 연구 기간 동안 경기도 자동심장충격기 중 일반인 활용이 가능한 자동심장충격기 설치 수는 2019년 8,626대, 202년 9,166대, 2021년 9,066대, 2022년 10,578대로 증가하였다. 시·군·구별 거주인구 10,000명당 자동심장충격기 설치비도 2019년 6.52대, 2020년 6.83대, 2021년 6.68대, 2022년 7.78개로 약 1.2배 증가한 것을 확인했다. 응급실에 내원한 심정지 환자 발생비도 2019년 4.98건, 2020년 4.84건, 2021년 5.16건, 2022년 7.21건으로 약 1.4배 증가하였다. _x000D_ 사회경제적 수준에 따른 자동심장충격기 설치 수는 사회경제적 수준이 낮아질수록 감소하였으며 특히 거주인구 10,000명당 주거지역의 자동심장충격기 설치 수는 사회경제적 수준이 낮을수록 감소하였다. 자동심장충격기 사용 건수는 사회경제적 요인에 따른 차이가 없었으나 거주인구 10,000명당 응급실 내원 심정지 환자 발생비는 사회경제적 수준이 낮아질수록 증가하였다._x000D_ _x000D_ 결론 : 사회경제적 수준이 낮을수록 상시 활용이 가능한 주거지역의 자동심장충격기 수가 감소하였으며 심정지 발생비는 증가하는 유의적 연관성을 확인할 수 있었다. 경기도 응급의료취약지 5개 시·군은 사회경제적 수준이 가장 낮은 그룹에 속하므로 안전한 지역을 만들고자 유기적인 인프라 구축 및 지역주민의 자동심장충격기 사용을 높이기 위한 교육프로그램 개발 등 지역맞춤형 방안 모색이 필요하다._x000D_ _x000D_ _x000D_ 핵심어: 자동심장충격기, 급성심장정지, 사회경제적 수준, 지역박탈지수_x000D_ _x000D_ _x000D_ _x000D_ _x000D_ _x000D_ _x000D_ _x000D_ _x000D_ _x000D_ _x000D_ _x000D_ _x000D_ _x000D_ _x000D_ _x000D_ _x000D_ _x000D_ _x000D_ |Background : In 2021, 23% of cases of sudden cardiac arrest occurred in Gyeonggi Province. It is well-established that if cardiopulmonary resuscitation (CPR) and defibrillation are administered within the golden time of 4 minutes, the survival rate for sudden cardiac arrest patients can be increased up to 70%. Immediate application of automated external defibrillators (AEDs) upon discovery of a patient also leads to higher survival rates, favorable neurological outcomes, and increased discharge rates. This study aims to analyze the installation and usage of AEDs in Gyeonggi Province, with a focus on understanding their association with socioeconomic status. The goal is to utilize the findings as basic data for developing community programs that enable easy access and use of AEDs by all local residents._x000D_ _x000D_ Methods : Data on the location and usage of AEDs in Gyeonggi Province from 2019 to 2022 were obtained from the National Emergency Medical Center's Emergency Medical Statistics Yearbook and intranet registration records. AEDs installed in 119 ambulances and medical institution vehicles for specific purposes were excluded from the study. Survival rates of cardiac arrest patients admitted to emergency rooms were analyzed using data from the National Emergency Department Information System (NEDIS). The study employed the Regional Deprivation Index as an indicator of socioeconomic status, categorized into quintiles, with higher indices indicating lower socioeconomic status._x000D_ _x000D_ Results : Over the study period, the number of AEDs available for public use in Gyeonggi Province increased from 8,626 units in 2019 to 10,578 units in 2022. The installation rate of AEDs per 10,000 residents also rose from 6.52 units in 2019 to 7.78 units in 2022. The incidence of cardiac arrest cases admitted to emergency rooms increased approximately 1.4 times from 2019 to 2022. The installation of AEDs showed a negative association with socioeconomic status, particularly in residential areas, where lower socioeconomic status was associated with fewer AED installations. While AED usage did not show significant differences based on socioeconomic factors, the incidence of emergency room admissions for cardiac arrest increased in areas with lower socioeconomic status._x000D_ _x000D_ Conclusion : Lower socioeconomic status was significantly associated with a decrease in the number of continuously available AEDs in residential areas and a significant increase in the incidence of cardiac arrest. Considering that five cities and counties in Gyeonggi Province are identified as areas with the lowest socioeconomic status, tailored strategies such as infrastructure development and community programs should be explored to enhance AED utilization and create safer environments in these emergency medical vulnerable regions_x000D_ _x000D_ Keywords: Public access defibrillator, Out-of-hospital cardiac arrest, Socioeconomic status, Regional Deprivation index_x000D_ _x000D_
학위논문(석사)--보건학과,2024. 2
Keywords: 급성심장정지; 사회경제적 수준; 자동심장충격기; 지역박탈지수